Diversity of Shiga toxin transducing phages in Escherichia coli O145:H28 and the different Shiga toxin 2 production levels associated with short- or long-tailed phages - Nakamura, Keiji; Taniguchi, Itsuki; Gotoh, Yasuhiro; Isobe, Junko; Kimata, Keiko; Igawa, Yukiko; Kitahashi, Tomoko; Takahashi, Yohei; Nomoto, Ryohei; Iwabuchi, Kaori; Morimoto, Yo; Iyoda, Sunao; et al. (Frontiers in Microbiology, 2024)
Shiga toxin (Stx)-producing Escherichia coli (STEC) causes serious gastrointestinal illness, including hemorrhagic colitis and hemolytic uremic syndrome. Two types of Stxs (Stx1 and Stx2) are known and both are encoded by bacteriophages (Stx phages), but the production of Stx2 is known to be a major risk factor for severe STEC infections. The production of Stx2, but not Stx1, is tightly coupled with the induction of Stx phages, and Stx2 production levels vary between STEC strains even within the same serotype. Here, we analyzed the genomic diversity of all Stx phages in 71 strains representing the entire O145:H28 lineage, one of the often highly pathogenic STECs, and the relationship between the variations in Stx phage genomes and the levels of Stx2 production by host strains. Our analysis reveals highly dynamic natures of Stx phages in O145:H28, including the independent acquisition of similar Stx phages by different sublineages, the recent transfer of Stx phage between different sublineages, and the frequent gain and loss of Stx phages in some sublineages. We also show the association of the Stx2 phage types with the Stx2 production levels of host strains: strains carrying short-tailed Stx2 phages exhibited significantly higher Stx2 production levels than those carrying long-tailed Stx2 phages. Detailed analyses of the Stx2 phage genomes revealed that both of short-and long-tailed phages exhibited sequence diversification and they were divided into two groups, respectively, based on the sequence similarity of the phage early region encoding genes responsible for phage induction, short-tailed phages contained early regions clearly different in genetic organization from those in long-tailed phages. Therefore, the variations in the early regions between short- and long-tailed Stx2 phages appeared to be linked to a striking difference in Stx2 production levels in their host strains. These results broaden our understanding of the diversification and dynamism of Stx phages in O145:H28 and the association of Stx2 phage types with the Stx2 production level in this STEC lineage.